PEMERIKSAAN CEMARAN Salmonella sp. PADA DAGING AYAM POTONG YANG DIPERDAGANGKAN DI PASAR SUKARAMAI KECAMATAN MEDAN AREA KOTA MEDAN - Banjarnahor, Irene; Nurtjahja, Kiki; Fauziah, Ida (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2015)
This reseach aims to determine the presence of Salmonella sp. In chicken meat sold in both markets. The study was conducted by taking samples of chicken meat in each market as much as 50 grams. In the Sukaramai market, samples were taken from three locations, namely location I, II, III and one location from Carrefour supermarket. The bacteria contamination test was performed by counting the number of bacteria each sample with Plat Count Agar (PCA) method, each sample was diluted and cultured on 10-1 dilution. Deuteronomy is done four times. Then proceed with biochemical test. The results showed that all four samples of Salmonella sp. From Sukaramai traditional market contaminated with pathogen bacteria with the average amount of Salmonella as much as 1.7 X 102 from the overall location I, II, and III and also found contaminant bacteria that can be a pathogen while from Carrefour supermarkets not found Salmonella.